Genetic variability and character association studies in Urdbean (Vigna mungo L.) under irrigated and rainfed conditions of Jammu region - Aman; Anjani Kumar Singh; Sanjeev Kumar; Manmohan Sharma; Neeraj Gupta (Annals of Agricultural Research, 2022)
The present investigation was carried out during Kharif 2020 at three locations viz. SKUAST-J, Chatha, Arid Centre for Rainfed Agriculture, Rakhdhiansar and Pulses Research Sub-Station, Samba for estimating genetic variability parameters and to outline the association of grain yield with yield contributing traits. The presence of significant genetic variation was revealed by analysis of variance among urdbean genotypes in each environment as well as on pooled basis.Pooled estimates of components of genetic variance revealed that phenotypic variance was relatively higher than genotypic variance for all the morpho-physiological traits implying the role of the environment in the expression of such traits. High heritability coupled with high genetic advance as percentage of mean was observed for number of primary branches per plant, number of clusters per plant, number of pods per cluster, number of pods per plant, pod length, number of seeds per pod, 1000 grain weight,grain yield per plant, biological yield per plant and harvest index indicating that these parameters are governed by additive-gene action and direct selection is effective for improving such traits. Grain yield per plant was found positively and significantly correlated with number of primary branches per plant, number of clusters per plant, number of pods per cluster, number of pods per plant, number of seeds per pod, pod length, test weight, biological yield and harvest index which revealed the importance of these characters indetermining the grain yield per plant.